Summertime thermal conditions and senior resident behaviors in public housing: A case study in Elizabeth, NJ, USA. (15th January 2020) - Tsoulou, Ioanna; Andrews, Clinton J.; He, Ruikang; Mainelis, Gediminas; Senick, Jennifer
Abstract: As heat waves become more extreme, there is a growing concern for the health of elderly city dwellers who have poor living conditions and limited access to resources. Much research has documented socioeconomic links to heat vulnerability, but limited studies have investigated the detailed living conditions of vulnerable populations, despite increasing requests from local communities. In this paper, we examine the summertime thermal performance of 24 senior apartments within 3 public housing sites (2 conventional multifamily and 1 LEED-rated building), and the seniors' adaptive responses in Elizabeth, NJ, USA. Time-series data were collected from sensors, interviews and observations on the thermal environment and behavior, from May–October 2017. Our multi-level, occupant-centric approach utilizes the indoor heat index as a proxy for heat stress, against site and building characteristics, and environmental and personal variables. Panel regressions show thermal variations among sites/apartments and illustrate the significant effect of actions, such as window opening and air conditioner use. Results also show how the seniors' adaptive responses vary by site; residents with central air-conditioning use it, while residents from the two older sites engage in a wider range of adaptive actions, and in some cases achieve similar indoor heat indexes as apartments from the green building. Indoor heat stress experienced by low-income seniors can be greatly reduced through cost-effective strategies that target individual behaviors and outdoor amenities. This implies the need for integrated solutions to the heat waves problem across scales; including changes to residents' habits, building envelopes, building operations, and outdoor spaces. Graphical abstract: Image 1 Highlights: A summer-long study of indoor thermal performance and occupant behaviors in senior public housing sites is conducted. The multi-level approach examines indoor heat against environmental, site, apartment, personal and behavioral variables. Behaviors and site have the strongest effect over the indoor heat index. Behaviors vary significantly across sites with different outdoor amenities and building envelopes. Heat adaptation strategies should jointly consider the residents' habits, building modifications and outdoor alterations.